2012
DOI: 10.1590/s0104-71832012000200002
|View full text |Cite
|
Sign up to set email alerts
|

Tecendo a tradição e valorizando o conhecimento tradicional na Amazônia: o caso da "linha do tucum"

Abstract: O artigo apresenta um estudo de caso na comunidade extrativista Céu do Juruá, no Amazonas, sobre processos de confecção de uma linha a partir das folhas da palmeira do tucum, espécie endêmica da região amazônica. Todo o preparo da linha bem como suas diferentes formas de utilização expressam modos peculiares de sociabilidade e de produção e transmissão de um conhecimento tradicional. A linha e todos os produtos gerados a partir dela são biodegradáveis, não representando riscos para os ciclos de vida na florest… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
6
0
3

Year Published

2014
2014
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 1 publication
0
6
0
3
Order By: Relevance
“…The Tucum (Astrocaryum huaimi) was mentioned in the use of handicraft and food for humans and pets. (ABREU & NUNES, 2012) reported that A. chambira (from the same genus as the Tucum) is used in construction, handicraft, cosmetics, medicine and food for animals.…”
Section: Resultsmentioning
confidence: 99%
“…The Tucum (Astrocaryum huaimi) was mentioned in the use of handicraft and food for humans and pets. (ABREU & NUNES, 2012) reported that A. chambira (from the same genus as the Tucum) is used in construction, handicraft, cosmetics, medicine and food for animals.…”
Section: Resultsmentioning
confidence: 99%
“…It can be divided into four stages: collecting the leaves, removing the fiber (which is referred as "linen" by them), combing and pulling the "linen" and spinning the yarn (Fig. 8) [14,37]. A basic characterization of this handcrafted yarn is shown in Table 3.…”
Section: Yarn Characterizationmentioning
confidence: 99%
“…In Brazil, more specifically in the community "Ceu do Jurua", located in the state of Amazonas, the palm A. chambira is known as "Tucum" and therefore its fibers as "Tucum fibers". The people of that region have a traditional knowledge passed from generation to generation of fiber extraction and handmade spinning, resulting in a yarn known locally as "Tucum Yarn", with which they develop many handcraft products [14].…”
Section: Introductionmentioning
confidence: 99%
“…A parte folhosa é desprezada. Lava-se o "linho", que é a fibra que acabou de ser extraída da folha, com sabão e coloca-se para secar estendido no varal.Quando seco pode-se tingir naturalmente ou não(NUNES, 2009;NUNES, 2012). c) Pentear e puxar o "linho" Penteia-se o linho seco com pente ou escova.…”
unclassified
“…O que sobra na escova é guardado para diversos fins: como enchimento de travesseiro, como bucha para banho ou lavagem de louça e para fazer bonecas. A etapa de puxar o linho consiste em puxá-lo devagar com as pontas dos dedos da mão até se obter um fio da grossura desejada(NUNES, 2009;NUNES, 2012). d) Fiar e urdir a linhaCom o auxílio do fuso de madeira, começa-se a etapa de urdir a linha.…”
unclassified